Microwave-assisted green approach for graft copolymerization of l-lactic acid onto starch - Salimi, Kouroush; Topuzogullari, Murat; Dincer, Sevil; Aydin, Halil Murat; Piskin, Erhan (WILEY, 2016)
Poly l-lactic acid grafted starch (St-g-PLA) copolymers were directly synthesized under microwave irradiation by using sodium hydroxide (NaOH) and stannous 2-ethyl hexanoate acting as a catalyst, without the use of toxic solvents. The product were characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (C-13 CP/MAS NMR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA-DTG). SEM analysis indicated that microwave heating had a considerable effect on the interfacial adhesion between PLA and starch. Thermogravimetric analysis (TGA-DTG) revealed that copolymers exhibited better thermal stability. Maximum PLA grafting was achieved with the following reaction conditions: 450W microwave power, monomer ratio of 1:5 and 0.4M of NaOH. This study demonstrates that it is possible to obtain St-g-PLA copolymers with better processing characteristics and smaller sizes via microwave-assisted synthesis. The applied procedure is an interesting green synthesis method for the production of biodegradable materials used in a diverse range of applications. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42937.
Keywords: graft copolymerization; lactic acid; microwave heating; starch; INITIATED SYNTHESIS; G-PAM; FLOCCULANT; BLENDS; MICROSTRUCTURE; POLYMERIZATION; METHACRYLATE; IRRADIATION; PARAMETERS; WATER; Polymer Science